Prioritas Pengembangan dan Pengelolaan Jaringan Irigasi Tersier di D.I. Yogyakarta Menggunakan Multiple Attribute Decision Making - Ansita Gupitakingkin Pradipta; Murtiningrum Murtiningrum; Niko Windy Dwi Febriyan; Fathi Alfinur Rizqi; Ngadisih Ngadisih (Balai Teknik Irigasi, 2020)
There are five pillars in the irrigation network management, one of them is the improvement of irrigation network facilities and infrastructure. The improvement of irrigation network facilities and infrastructure is divided into two activities, namely development and management. Related to these activities, there are many locations in the irrigation area that require prior handling. This study purposed to analyze the priority of ten irrigation systems of district authority spread over D.I. Yogyakarta for optimizing the implementation of management of irrigation networks. The analysis used (Multiple Attribute Decision Making) MADM which consists of SAW, WP, TOPSIS, Electre and AHP methods. Five parameters used in the analysis, including main irrigation network infrastructure, tertiary irrigation network infrastructure, water availability, service area, and crop productivity. The study proved that the tertiary irrigation network in 10 irrigation systems of district authority in D.I. Yogyakarta suffered moderate to severe damage in a number of 65 locations. There were 11 locations that always appear at the top of each MADM, which were priority proposals for irrigation network development and management activities. In addition, there was a tendency that the higher the irrigated area, the higher the priority of development or management of a location. If there are several proposed locations with similar conditions, the determination of priorities can be determined based on the irrigated area.